2020
DOI: 10.1016/j.jot.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of four tibial fixation techniques for meniscal root sutures in posterior medial meniscus root repair: A porcine study

Abstract: Objective This study hypothesized that the suture anchor of tibial fixation method of PMMR repair technique is the main factor which reduce the gap formation or over displacement of tear site in initial healing, and then investigated the fixation stability of 4 different tibial fixations through cyclic and ultimate failure load testing of meniscal root sutures. Methods Twenty-four porcine tibiae with intact medial meniscus roots were randomly assigned into 4 groups: tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Furthermore, we simultaneously use the pull-out repair technique. A study using pig knees found that the failure load of the pull-out repair using a washer was 189.9 N. 22 Thus, our method can apply stronger traction.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, we simultaneously use the pull-out repair technique. A study using pig knees found that the failure load of the pull-out repair using a washer was 189.9 N. 22 Thus, our method can apply stronger traction.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, a study by Wu et al showed that anchor suture had lower maximum load and stiffness compared with transtibial technique but the mean elongation was less. The reason might be because of the different techniques and the study was done with porcine knees which are different from human [64].…”
Section: Suture Anchor Techniquementioning
confidence: 99%
“…The first approaches to quantify meniscal tear gapping were simplified uniaxial ex vivo tensile tests using standard testing machines. [20][21][22][23][24][25][26][27][28] Other groups have utilized magnetic resonance imaging (MRI) [29][30][31][32] to assess meniscal gapping in vivo under static knee flexion angles. Dürselen et al were one of the first to identify gapping under moderate dynamic loading conditions by means of a knee simulator 33,34 and found a significant gapping behaviour of longitudinal tears.…”
mentioning
confidence: 99%
“…By contrast, McCulloch and Lin et al in their studies rather observed a compression of longitudinal tears under gait-like conditions, 35,36 leading to significant debate. From a technological point of view, meniscus gapping was assessed optically by movement deflection, [20][21][22][23][24][25][26][27][28] MRI, [29][30][31][32] arthroscopically 33,34 and Roentgen stereophotogrammetric analysis (RSA). 35,36 To the best of the authors' knowledge, meniscal tear gapping has only been studied independently of the related tibiofemoral contact pressure, which is an important contributor to a healthy knee joint.…”
mentioning
confidence: 99%